Junior doctors' on call activities: differences in workload and work patterns among grades. Issue 6762 (24th November 1990) - Turnbull, N B; Miles, N A; Gallen, I W
Abstract : OBJECTIVE--To examine the workload and work patterns of junior doctors of all grades while on call. DESIGN--Pilot study of activity data self recorded by junior doctors, with the help of students during busy periods. SETTING--A general surgical firm and a general medical firm based at University Hospital, Nottingham. SUBJECTS--Four registrars, three senior house officers, and five preregistration house officers. RESULTS--Senior house officers and preregistration house officers spent nearly half of all their on call duty time working, but less than half of that time was spent in direct contact with patients. Registrars were on call more often than the house officers but spent less than one fifth of their on call duty time working, and almost two thirds of that time was spent in direct contact with patients. CONCLUSIONS--Workload while on duty is excessive for both senior and preregistration house officers. Changes in some administrative procedures and employment of more non-medical staff during on call periods might reduce the time spent on non-clinical activities, thereby reducing the overall workload and allowing more time for patient contact.